Pengaruh Konsep Diri dan Kemandirian Belajar terhadap Hasil Belajar Matematika Siswa SMP - Liana Widya Astuti; Heni Pujiastuti (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This research aims to see how much influence self-concept and learning independence have on mathematics learning outcomes. The method used is a survey method with a quantitative approach. The sample in this study were students of Class VIII B MTs. Daar El-Huda as many as 32 students. Data collection is done by giving a questionnaire. The data used are primary data and secondary data. Primary data includes 2 variables (self-concept and learning independence) which were collected with previously validated instruments. Secondary data is the result of students' mathematics learning obtained from mathematics teachers. Based on the results of the study, it can be concluded that first, there is an effect of self-concept and independent learning together on learning outcomes of mathematics. The contribution of self-concept and learning independence to mathematics learning outcomes is 96.1% and the remaining 3.9% are other variables that contribute besides self-concept and learning independence. Second, there is the effect of self-concept on mathematics learning outcomes. Third, there is the influence of independent learning on mathematics learning outcomes.